2015
DOI: 10.1007/s00167-015-3712-7
|View full text |Cite
|
Sign up to set email alerts
|

Moderate clinical improvement after revision arthroplasty of the severely stiff knee

Abstract: Therapeutic studies-case series with no comparison group, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Particularly arthroscopy represents a significant risk factor for the development of arthrofibrosis [13, 14]. In the investigated patient collective, secondary diseases favouring arthrofibrosis [1, 15] were found in the form of obesity (26.3%), obesity with hyperuricemia (10.5%), hyperuricemia (5.3%) and pre-existing neurological diseases (10.5%). However, no significant accumulation of secondary diseases could be detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly arthroscopy represents a significant risk factor for the development of arthrofibrosis [13, 14]. In the investigated patient collective, secondary diseases favouring arthrofibrosis [1, 15] were found in the form of obesity (26.3%), obesity with hyperuricemia (10.5%), hyperuricemia (5.3%) and pre-existing neurological diseases (10.5%). However, no significant accumulation of secondary diseases could be detected.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical pathology corresponds to stiff-knee or arthrofibrosis, although a precise definition of the disease is still lacking. Incorrect implant positioning and instabilities can be possible causes [1]. A hypothesis for the development of arthrofibrosis is a low-grade infection [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…But the improvement was modest (70-72). However, there has been a marked improvement in a 2-year clinical outcome of severe stiffness cases, with the use of Genesis and Legion stemmed condylar prostheses (73). In 2016, Donaldson et al even presented a novel technique for improving stiffness, named by "sloppy" revision (74).…”
Section: Discussionmentioning
confidence: 99%
“…It is still important to isolate the cause, otherwise revision may only provide modest improvements. 3,3638 Keeney et al suggested that revision surgery should be limited to patients with severely restricted motion and extensive flexion contractures. They found that in these cases the postoperative improvements are likely to be limited as a consequence of the severity of stiffness.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Table 5 summarizes the main data from the most important papers reported in recent literature on revision arthroplasty in the stiff TKA. 3638…”
Section: Treatment Modalitiesmentioning
confidence: 99%